A negative correlation between self-regulation learning strategies and emotional intelligence: a new finding - Karimpour, Shahin; Sayad, Arezou; Aerab Sheibani, Khadije (Researcher Bulletin of Medical Sciences, 2019)
Background and Objective: In self-regulation learning, learners will have personal control over the learning process, and emotional intelligence refers to personal control of emotions and feelings of self-regulation. The present study seeks to determine the relationship between the components of self-regulation learning and emotional intelligence. Materials and Methods: A sample of 200 students (100 females and 100 males) who were studying at Tehran and Shahid Beheshti University of Medical Sciences participated in the study. Self-regulation learning scale and Goleman's emotional intelligence questionnaire were used. Data were analyzed using Pearson correlation coefficient and multivariate regression tests. Results: The results of regression analysis showed that the correlation coefficient between self-regulation learning and emotional intelligence was negative (r = -0.171 and p = 0.015). Among the self-regulation learning components, the correlation coefficient between emotional intelligence and organization and transfer components (r = -0.144, p= 0.041) and self-efficacy (p = 0.011, r = -0.18) were significant. Conclusion: The negative relationship in the present research suggests that feelings emotions for expressing themselves and facilitating their presentation emerge in the easiest, happiest and most successful way of thinking and harmony. But self-regulation learning is a way to repeat and practice, persevere and tolerate problems to reach logical thinking.